Wanprestasi Terhadap Akta Perjanjian Pengikatan Jual Beli (PPJB) Rumah Susun yang Dibuat oleh Notaris - Palar, Vicky Caesar Elang; Mekka, Mohamad Fajri (Fakultas Syariah INSURI Ponorogo, 2023)
Property sale and purchase transactions such as flats are transactions with large nominal values. The related parties must make a binding sale and purchase agreement as a means of legal protection for both parties in the event of a default against PPJB made by a notary so that the letter becomes official and safe. This study aims to determine the causal factors, and the legal protection of default of the sale and purchase binding deed (PPJB) of the apartment made by a notary. In addition, PPJB is also a letter made by a notary and as legal protection for consumers and is officially made by a notary.